Allogeneic human dermal fibroblasts are viable in peripheral blood mononuclear co-culture - Restu Syamsul Hadi; Indra Kusuma; Yurika Sandra (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDTransplanted allogeneic dermal fibroblasts retain stem cell subpopulations, and are easily isolated, expanded and stored using standard techniques. Their potential for regenerative therapy of chronic wounds should be evaluated. The aim of this study was to determine allogeneic fibroblast viability in the presence of peripheral blood mononuclear cells (PBMC).METHODSIn this experimental study, fibroblasts were isolated from foreskin explants, expanded in the presence of serum, and stored using slow-freezing. We used one intervention group of allogeneic fibroblasts co-cultured with PBMC and 2 control groups of separate fibroblast and PBMC cultures.Fibroblasts were characterized by their collagen secretion and octamer-binding transcription factor 4 (OCT4) expression. Viability was evaluated using water soluble tetrazolium-1 (WST-1) proliferation assay. Absorbances were measured at 450 nm. Data analysis was performed by student’s paired t-test.RESULTSDermal fibroblasts were shown to secrete collagen, express OCT4, be recoverable after cryopreservation, and become attached to the culture dish in a co-culture with PBMC. Co-cultured and control fibroblasts had no significantly different cell viabilities (p>0.05). Calculated viable cell numbers increased 1.8 and 5.1- fold, respectively, at days 2 and 4 in vitro. Both groups showed comparable doubling times at days 2 and 4 in vitro. PBMC did not interfere with allogeneic fibroblast viability and proliferative capacityCONCLUSIONSAllogeneic fibroblasts remain viable and proliferate in the presence of host PBMC. Future research should evaluate allogeneic human dermal fibroblast competency in clinical settings. Dermal fibroblasts are a potential source for cell therapy in chronic wound management.